Aluminum alloy plate for can lids
Patent Information
- Application Number
- JP2022036491
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-09
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2042-03-09
Smart Images

Figure 0007652730000005 
Figure 0007652730000006 
Figure 0007652730000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an aluminum alloy sheet for can ends. [Background technology]
[0002] In recent years, there has been a demand for aluminum alloy sheets with low CO2 emissions during the manufacturing process due to growing environmental awareness. In the aluminum rolling process, the composition of new aluminum ingots in the casting process indirectly contributes greatly to CO2 emissions.
[0003] The production of primary aluminum ingots uses a large amount of electricity during the refining process, which leads to large amounts of CO2 emissions. Therefore, reducing the amount of primary aluminum ingots mixed and increasing the horizontal recycling rate will lead to a reduction in CO2 emissions in the production of aluminum alloy sheets.
[0004] It is generally said that CO2 emissions from remelting and casting aluminum scrap can be reduced to about one-thirtieth of that from producing new aluminum ingots. In particular, the production volume of aluminum alloy sheets for beverage cans used around the world is extremely large, and further improving the horizontal recycling rate of these sheets has great significance in reducing the environmental impact.
[0005] Among these, can ends made of 5182 aluminum alloy (AA5182 alloy) have lower upper limits for the composition standards of Si, Fe, Cu, Mn, etc. than can bodies made of 3104 aluminum alloy (AA3104 alloy), making it difficult to mix scrap derived from can materials that contain 3104 aluminum alloy.
[0006] For example, if can scrap (UBC: Used Beverage Can) generated in the city is mixed as is, the weight ratio of the can body to the can lid will result in a higher content of 3104 aluminum alloy components, which will easily exceed the upper limit of the content of 5182 aluminum alloy, making it necessary to dilute the components with virgin metal.
[0007] Therefore, compared to aluminum alloy sheets for can bodies, aluminum alloy sheets for can ends use more virgin metal and have the composition adjusted to 5182 aluminum alloy, resulting in a low recycling rate. Therefore, by changing can ends to alloys whose composition is easily mixed with 3104 aluminum alloy, the usage rate of virgin metal for can ends can be significantly reduced.
[0008] In Patent Documents 1 to 5, aluminum alloy sheets for can ends have been developed that have compositions relatively close to those of 3104 aluminum alloy, which has excellent recyclability. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2001-73106 A [Patent Document 2] Japanese Patent Application Publication No. 9-070925 [Patent Document 3] Japanese Patent Application Publication No. 11-269594 [Patent Document 4] JP 2000-160273 A [Patent Document 5] JP 2016-160511 A Summary of the Invention [Problem to be solved by the invention]
[0010] The challenge in making the alloy for can lids closer to the 3104 aluminum alloy is that it reduces the pressure resistance of the can lids and the toughness of the material. The pressure resistance of a can lid is the internal pressure value when the can lid is inverted against the pressure inside the can, and is the resistance value when the internal pressure of the can increases unexpectedly due to a change in the external environment.
[0011] In particular, positive pressure cans for beer and carbonated beverages require high pressure resistance. Generally, the stronger the material and the thicker the plate, the higher the pressure resistance. For this reason, high-strength 5182 aluminum alloy with a high magnesium content is used for the lids of positive pressure cans.
[0012] In contrast, if the conventional 3104 aluminum alloy is used for can lids, the pressure resistance is significantly reduced, and there is a high possibility that the lid will invert and the contents will leak if the internal pressure of the can suddenly increases. Also, if the plate thickness is made too thick in order to increase the pressure resistance, it will lead to an increase in the weight and cost of the lid.
[0013] The toughness of the material affects the formability and opening ability of the lid. If the material has low toughness, forming cracks may occur, especially at the rivet part of the lid. Also, if the internal pressure of the can suddenly increases, cracks may occur at the score part, increasing the risk of the contents of the can leaking.
[0014] However, aluminum alloy sheets for can ends that have a composition relatively close to that of the conventional 3104 aluminum alloy do not satisfy either or both of the above two issues, i.e., material strength (pressure resistance of the end) and toughness (formability and openability).
[0015] An object of one aspect of the present disclosure is to provide an aluminum alloy sheet for can ends that can achieve both high strength and high toughness while incorporating scrap raw material derived from can stock. [Means for solving the problem]
[0016] One embodiment of the present disclosure is a steel sheet having a silicon (Si) content of 0.10 mass% or more and 0.60 mass% or less, an iron (Fe) content of 0.20 mass% or more and 0.70 mass% or less, a copper (Cu) content of 0.10 mass% or more and 0.40 mass% or less, a manganese (Mn) content of 0.5 mass% or more and 1.2 mass% or less, a magnesium (Mg) content of 1.1 mass% or more and 4.0 mass% or less, and a 0.2% proof stress σ 0.2 , tensile strength σ B , and the average value of 0.2% proof stress and tensile strength σ fm The aluminum alloy sheet for can ends satisfies the following formula (1): σ fm / (σ 0.2 / σ B ) ≥ 350MPa (1)
[0017] According to this configuration, it is possible to obtain both high strength and high toughness of the aluminum alloy sheet while blending scrap raw material derived from can material. That is, it is possible to blend a certain amount of 3104 aluminum alloy scrap for can body, and it is possible to reduce the usage rate of new ingots and the amount of CO2 emissions. Furthermore, it is possible to obtain an aluminum alloy sheet for can ends that can be used for positive pressure can ends that require high pressure resistance. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1A is a schematic perspective view of the Erichsen Cup, and FIG. 1B is a schematic plan view of the Erichsen Cup. [Diagram 2] FIG. 2 is a graph showing an example of the measurement results of the sidewall height of the Erichsen Cup. [Diagram 3] FIG. 3 is a graph showing the relationship between t2.27×σfm / (σ0.2 / σB) and the withstand voltage in the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, embodiments to which the present disclosure is applied will be described with reference to the drawings. [1. First embodiment] [1-1. Configuration] <Composition> The aluminum alloy sheet for can ends (hereinafter also simply referred to as "alloy sheet") of the present disclosure contains aluminum (Al), silicon (Si), iron (Fe), copper (Cu), manganese (Mn) and magnesium (Mg).
[0020] The lower limit of the Si content is 0.10 mass%, preferably 0.20 mass%. If the Si content is less than 0.10 mass%, the amount of Si precipitated in the processing heat of the cold rolling after the hot rolling and solution treatment decreases, and the strength of the alloy sheet may be insufficient.
[0021] In addition, the average value of the Si content standard of the 3104 aluminum alloy specified in JIS-H-4000:2014 is 0.30 mass%, and the average value of the Si content standard of the 5182 aluminum alloy specified in JIS-H-4000:2014 is 0.10 mass%. Therefore, by making the Si content 0.20 mass% or more, a large amount of 3104 aluminum alloy scrap can be blended.
[0022] The upper limit of the Si content is 0.60 mass%, and preferably 0.40 mass%. If the Si content exceeds 0.60 mass%, the number of Mg2Si particles increases, and the toughness of the alloy plate decreases.
[0023] The lower limit of the Fe content is 0.20% by mass, and preferably 0.30% by mass. The average Fe content standard of 3104 aluminum alloy is 0.40% by mass, and the average Fe content standard of 5182 aluminum alloy is 0.18% by mass. Therefore, by making the Fe content 0.30% by mass or more, a large amount of 3104 aluminum alloy scrap can be blended.
[0024] The upper limit of the Fe content is 0.70 mass%. If the Fe content exceeds 0.70 mass%, the amount of Al-Fe-Mn or Al-Fe-Mn-Si intermetallic compounds (i.e., second phase particles) increases. As a result, a crack propagation path is generated, and the toughness of the alloy plate decreases.
[0025] The lower limit of the Cu content is 0.10 mass%, preferably 0.11 mass%, and more preferably 0.20 mass%. If the Cu content is less than 0.10 mass%, Cu that increases the strength by solid solution or precipitation is insufficient, and the average strength of the alloy sheet is reduced. By precipitating Cu during the processing of cold rolling after hot rolling and solution treatment, the strength of the alloy sheet is significantly increased.
[0026] In addition, the average Cu content of the 3104 aluminum alloy is 0.15% by mass, and the average Cu content of the 5182 aluminum alloy is 0.075% by mass. Therefore, by making the Cu content 0.11% by mass or more, a large amount of 3104 aluminum alloy scrap can be blended.
[0027] The upper limit of the Cu content is 0.40 mass %. If the Cu content exceeds 0.40 mass %, the toughness of the alloy plate decreases.
[0028] The lower limit of the Mn content is 0.5 mass%, preferably 0.7 mass%, and more preferably 0.8 mass%. If the Mn content is less than 0.5 mass%, the amount of Mn that increases the strength by solid solution or precipitation is insufficient, and the average strength of the alloy sheet is reduced.
[0029] In addition, the average value of the Mn content standard of the 3104 aluminum alloy is 1.1 mass%, and the average value of the Mn content standard of the 5182 aluminum alloy is 0.35 mass%. Therefore, by making the Mn content 0.7 mass% or more, a large amount of 3104 aluminum alloy scrap can be blended.
[0030] The upper limit of the Mn content is 1.2 mass%, and preferably 1.0 mass%. If the Mn content exceeds 1.2 mass%, the amount of Al-Fe-Mn or Al-Fe-Mn-Si intermetallic compounds (i.e., second phase particles) increases. As a result, a crack propagation path is generated, and the toughness of the alloy plate decreases.
[0031] The lower limit of the Mg content is 1.1 mass%. If the Mg content is less than 1.1 mass%, the Mg that increases the strength by solid solution is insufficient, and the average strength of the alloy sheet decreases. By precipitating Mg during the processing of cold rolling after hot rolling and solution treatment, the strength of the alloy sheet increases significantly.
[0032] The upper limit of the Mg content is 4.0% by mass, and preferably 3.0% by mass. The average value of the Mg content standard of 3104 aluminum alloy is 1.05% by mass, and the average value of the Mg content standard of 5182 aluminum alloy is 4.5% by mass. Therefore, by making the Mg content 4.0% by mass or less, more preferably 3.0% by mass or less, it is possible to reduce the amount of additional Mg-containing raw material while mixing a large amount of 3104 aluminum alloy scrap.
[0033] The alloy plate may contain titanium (Ti). The upper limit of the Ti content is preferably 0.10 mass%. The ingot structure of the alloy plate is refined by including Ti. The alloy plate may also contain zinc (Zn). The upper limit of the Zn content is preferably 0.25 mass%. Furthermore, the alloy plate may contain chromium (Cr). The upper limit of the Cr content is preferably 0.10 mass%.
[0034] The alloy plate may contain unavoidable impurities to the extent that the performance of the alloy plate is not significantly impaired. That is, the alloy plate contains Si, Fe, Cu, Mn, and Mg in the above-mentioned ranges, with the remainder being aluminum and unavoidable impurities. The upper limit of the unavoidable impurities is preferably 0.15% by mass.
[0035] <Material strength and pressure resistance> 0.2% yield strength σ of the aluminum alloy plate of the present disclosure 0.2 , tensile strength σ B , and the average value of 0.2% proof stress and tensile strength σ fm satisfies the following formula (1). σ fm / (σ 0.2 / σ B ) ≥ 350MPa (1)
[0036] Empirically, the pressure resistance value of an aluminum alloy cover has a strong positive correlation with the value V of the following equation (3), which is expressed by the material strength of the aluminum alloy plate (i.e., the left side of equation (1)) and the plate thickness t. V=t 2.27 ×σ fm / (σ 0.2 / σ B) ···(3)
[0037] Therefore, the material strength of the alloy plate σ fm / (σ 0.2 / σ B ) is 350 MPa or more, a lid having a sufficient pressure resistance can be formed without significantly increasing the plate thickness.
[0038] The lower limit of the left side of formula (1) (i.e., the value of the right side of formula (1)) is more preferably 370 MPa. fm / (σ 0.2 / σ B ) to 370 MPa or more, the pressure resistance of the lid can be further increased.
[0039] 0.2% proof stress σ in formula (1) and formula (3) 0.2 and tensile strength σ B is measured by the method specified in JIS-Z-2241: 2011. The plate thickness t is measured, for example, with a micro gauge.
[0040] The pressure resistance of an aluminum alloy plate is measured, for example, by the following procedure. A shell formed from an aluminum alloy plate is fixed to a jig and internal pressure is applied. The internal pressure is gradually increased, and the internal pressure value at which the shell inverts (i.e., buckles) is taken as the pressure resistance value.
[0041] Specifically, a φ204 Fullform (B64) shaped shell mold is used to mold the shell. The internal pressure value is measured using VERSATILE TECHNOLOGY's Buckle & Missile Measuring Machine DV036E. In more detail, after fixing the molded shell with a special jig, the internal pressure is increased by program and the internal pressure value is read when the shell inverts. For example, the internal pressure is increased at a speed of approximately 175 kPa / s, and when it reaches approximately 350 kPa to 400 kPa, the internal pressure is increased at a speed of 10 kPa / s.
[0042] <Toughness> It is known that the formability of the lid and the force required to open the score (i.e., opening force) are affected by the toughness of the aluminum alloy plate.
[0043] (Number of repeated bending) A repeated bending test is one of the evaluation indexes for the toughness of an aluminum alloy plate. If the plate thickness is the same, the more repeated bending times the aluminum alloy plate is, the more excellent the toughness of the aluminum alloy plate is. The aluminum alloy plate of the present disclosure can achieve a good number of repeated bending times.
[0044] The repeated bending test is carried out according to the following procedure. For example, a rectangular test piece with a width of 12.5 mm and a length of 200 mm is processed so that the bending ridge line direction is in the rolling direction of the alloy plate. Both ends of this test piece are fixed with chucks, and a tension of 200 N is applied. In this state, the test piece is repeatedly bent by rotating one of the chucks 90° left and right, using a jig with a bending radius of 2.0 mm placed at the center of the length of the rectangular piece as a fulcrum, and the number of bends until the test piece breaks is measured.
[0045] The number of bendings is counted as one bending 90° to the left or right and then returning to the original 0° position (i.e. bending 90° and then bending back 90°). If it breaks midway, read the angle θ (0°-180°) and calculate the number of repeated bendings N using formula (4) below. In formula (4), N0 is the number of times it is bent 90° to the left or right and then returned to the original 0° position (i.e. the number of times it is bent 90° and then bent back 90°). N = N0 + Θ / 180 (4)
[0046] Repeated bending evaluation is disadvantageous as the plate thickness increases, so it is necessary to correct for the standard plate thickness. Therefore, the number of repeated bending times N is standardized by the following formula (5) with a plate thickness of 0.245 mm as the standard. s t (mm) is the thickness of the test piece. N s = N × t / 0.245 (5)
[0047] (second phase particles) Toughness is affected by strength and the distribution of second phase particles. In other words, the higher the strength and the higher the density of second phase particles, the lower the toughness. In particular, when the Mg and Si contents are high, Mg2Si particles are more likely to form. As a result, the Mg2Si particles become the starting point and propagation path of cracks, which affects the decrease in toughness.
[0048] The aluminum alloy sheet of the present disclosure has a surface layer with an area of 0.3 μm in a cross section parallel to the sheet surface. 2 It is preferable that the ratio of the total area of the cross section of the Mg2Si particles is 1.0% or less.
[0049] The area ratio of Mg2Si particles can be measured by the following method. The surface of the measurement sample to be measured (i.e., the plate surface of the alloy plate) is polished. The polishing depth is about 1% of the plate thickness of the measurement sample.
[0050] The polished surface (i.e., a cross section parallel to the plate surface at the surface layer of the alloy plate) is observed using a scanning electron microscope (SEM) to obtain 10 fields of view. The magnification of the SEM is 500 times, and the range of one field of view is 0.48 mm 2 The image is then taken and a COMPO (backscattered electron composition image) is obtained.
[0051] The photographed COMPO is analyzed using the image analysis software ImageJ. Specifically, the most frequent brightness value of the image in 256 gradations is taken as the background brightness, and particles with brightness lower than the brightness of the most frequent value minus 30 are determined to be Mg2Si particles.
[0052] Among the determined Mg2Si particles, 0.3 μm 2 The total area of particles with an area of 0.3 μm or more was calculated and divided by the photographed area. 2 The ratio of the total area of the cross section of the above Mg2Si particles is calculated.
[0053] (Ear rate) The number of repeated bending cycles also affects the texture, and the higher the concentration of cube orientation, the better. The concentration of cube orientation is reflected in the shape of the ears of the Erichsen cup 1 formed from an aluminum alloy sheet by the Erichsen test, as shown in Figures 1A and 1B.
[0054] Specifically, it is suggested that the greater the relative sidewall height H in the 0° / 180° direction with respect to the rolling direction RD with respect to the sidewall height H (i.e., ear height) in the 45° direction with respect to the rolling direction RD of the aluminum alloy plate of the Erichsen Cup 1, the higher the degree of accumulation of the cube orientation. That is, the aluminum alloy plate of the present disclosure includes those having a relatively large degree of accumulation of the cube orientation and a high sidewall height H in the 0° / 180° direction.
[0055] The relative sidewall height in the 0° / 180° direction to the sidewall height in the 45° direction can be evaluated using an index called earing balance. The procedure for measuring the earing balance is explained below.
[0056] The ear ratio is expressed by the left side of the following equation (2). (h 0p -h 45p ) / h v ×100≧-7.0 (2)
[0057] In formula (2), h 0p is the average value of the maximum sidewall heights in the first region A1 around 0° and the second region A2 around 180° with respect to the rolling direction. The first region A1 is, for example, in the range of 0°±11° with respect to the rolling direction. The second region A2 is, for example, in the range of 180°±11° with respect to the rolling direction.
[0058] h 45p is the average value of the maximum sidewall heights in the third region A3 around 45°, the fourth region A4 around 135°, the fifth region A5 around 225°, and the sixth region A6 around 315° with respect to the rolling direction.
[0059] The third region A3 is, for example, in the range of 45°±22° with respect to the rolling direction. The fourth region A4 is, for example, in the range of 135°±22° with respect to the rolling direction. The fifth region A5 is, for example, in the range of 225°±22° with respect to the rolling direction. The sixth region A6 is, for example, in the range of 315°±22° with respect to the rolling direction.
[0060] h v is the average value of the minimum side wall height in each of the seventh region A7 from 0° to 45°, the eighth region A8 from 45° to 135°, the ninth region A9 from 135° to 180°, the tenth region A10 from 180° to 225°, the eleventh region A11 from 225° to 315°, and the twelfth region A12 from 315° to 360° relative to the rolling direction.
[0061] Figure 2 is a graph showing an example of the measurement results of the sidewall height of an Erichsen cup. The angles shown in Figure 2 are angles relative to the rolling direction. The distance from the center of the graph indicates the sidewall height.
[0062] In the figure, ad is the maximum value in the third region A3 to the sixth region A6, e and f are the maximum values in the first region A1 and the second region A2, and gl is the minimum value in the seventh region A7 to the twelfth region A12.
[0063] The Erichsen cup 1 is formed under the conditions of, for example, a blank diameter of 57 mm and a punch diameter of 33 mm. The sidewall height of the Erichsen cup is measured using, for example, a Roncoder EC1550 manufactured by Kosaka Laboratory Co., Ltd.
[0064] Specifically, a measurement probe is placed at the opening of the Erichsen cup with the rolling direction as the reference (0° / 180°), and the table on which the Erichsen cup is placed is rotated once to measure the opening height in the circumferential direction of 360°.
[0065] When formula (2) is satisfied, that is, when the earing ratio is -7.0% or more, the concentration of cube orientation increases, and as a result, the number of repeated bending cycles of the alloy sheet can be increased.
[0066] <Method of manufacturing aluminum alloy plate> The aluminum alloy plate of the present disclosure can be produced, for example, as follows: First, an aluminum alloy having the composition of the aluminum alloy plate of the present disclosure is subjected to semi-continuous casting (i.e., DC casting) according to a conventional method to produce an ingot.
[0067] Next, the surface of the ingot is chamfered. After that, the ingot is put into a soaking furnace and subjected to homogenization treatment. The temperature in the homogenization treatment is preferably, for example, 470° C. or more and 620° C. or less. The time for the homogenization treatment is preferably, for example, 1 hour or more and 20 hours or less.
[0068] When the homogenization temperature is 400°C or higher, segregation of the ingot structure is easily eliminated. Furthermore, when the homogenization temperature is 450°C or higher, Mg2Si particles are redissolved, and the strength and toughness of the alloy plate can be improved. Furthermore, when the homogenization temperature is 490°C or higher, more preferably 550°C or higher, the redissolution of Mg2Si particles is promoted, and the strength and toughness of the alloy plate can be further improved. On the other hand, when the homogenization temperature is 620°C or lower, local melting of the aluminum alloy is unlikely to occur.
[0069] If the homogenization treatment time is 1 hour or more, the temperature of the entire slab becomes uniform, segregation in the ingot structure is easily eliminated, and Mg2Si particles are easily redissolved. The longer the homogenization treatment time, the more the Mg2Si particles can be redissolved. However, if the homogenization treatment time exceeds 20 hours, the effect of the homogenization treatment becomes saturated.
[0070] After the homogenization treatment, the ingot is subjected to hot rolling. The hot rolling process includes a rough rolling process and a finish rolling process. In the rough rolling process, the ingot is processed into a plate material having a thickness of about several tens of mm by reverse rolling. In the finish rolling process, the thickness of the plate material is reduced to about several mm by, for example, tandem rolling, and the plate material is wound into a coil to form a hot rolled coil.
[0071] If the total reduction rate of the finish rolling is high, the recrystallized structure will be formed after coiling, and the degree of accumulation of the cube orientation can be increased. If the coiling temperature of the finish rolling is high, the recrystallized structure will be formed after coiling, and the degree of accumulation of the cube orientation can be increased.
[0072] Also, a high-strength alloy sheet can be obtained by subjecting hot-rolled coils to solution treatment to redissolve Mg, etc. For example, heat treatment (i.e., annealing) is performed using a continuous annealing furnace at a target actual temperature of 440°C or higher for 30 seconds or longer, and then forced cooling by air cooling or the like can be performed to effectively increase the strength of the alloy sheet.
[0073] Following the hot rolling, the plate material is cold rolled. In cold rolling, the hot rolled coil is rolled until the product plate thickness is reached. Cold rolling may be either single rolling or tandem rolling. In single cold rolling, rolling is preferably performed in multiple passes, such as two or more passes.
[0074] By setting the finishing temperature of cold rolling in the intermediate passes other than the final pass to 120°C or higher, Si, Cu and Mg are finely precipitated and age hardened, so that the strength of the alloy sheet can be increased. Furthermore, by setting the finishing temperature to 130°C or higher, the strength of the alloy sheet can be further increased.
[0075] The cold rolling reduction (i.e. the total reduction) is preferably 80% or more. When the cold rolling reduction is 80% or more, the strength of the alloy sheet can be increased. The lower the cold rolling reduction, the more the cube orientation remains. The cold rolling reduction is preferably 92% or less.
[0076] The cold rolling reduction ratio R (%) is calculated using the hot rolled sheet thickness t0 (mm) and the product thickness after cold rolling t1 (mm) according to the following formula (6). R = (t0-t1) / t0 × 100 (6)
[0077] The product thickness can be appropriately selected to obtain the desired pressure resistance. As shown in the above formula (3), the pressure resistance improves as the thickness increases. The product thickness is t 2.27 ×σfm / (σ 0.2 / σ B ) is preferably selected in the range of ≧14. As described above, according to the aluminum alloy sheet of the present disclosure, an increase in sheet thickness required to maintain high pressure resistance can be suppressed.
[0078] In addition, as long as the effects of the aluminum alloy sheet of the present disclosure are exhibited, in the above-mentioned method for producing an aluminum alloy sheet, annealing may be performed, for example, before or after cold rolling or between passes.
[0079] After the coils have been cold-rolled to the product thickness, they are pre-coated in a painting line, etc. The surface of the cold-rolled coils is degreased, cleaned, and chemically treated, and then painted, after which the paint is baked.
[0080] Chemical solutions such as chromate-based and zirconium-based are used in chemical conversion treatment. Epoxy-based and polyester-based paints are used. These can be selected according to the application. In the paint baking process, the coil is heated to a peak metal temperature (PMT) of 220°C to 270°C for approximately 30 seconds or less. The lower the PMT, the more the material recovery is suppressed, and the higher the strength of the alloy plate can be maintained.
[0081] [1-2. Effects] According to the embodiment described above in detail, the following effects can be obtained. (1a) It is possible to obtain both high strength and high toughness of aluminum alloy sheet while blending scrap raw material derived from can material. That is, it is possible to blend a certain amount of scrap 3104 aluminum alloy for can body, and it is possible to reduce the usage rate of new ingots and CO2 emissions. Furthermore, it is possible to obtain aluminum alloy sheet for can ends that can be used for positive pressure can ends that require high pressure resistance.
[0082] 2. Other embodiments Although the embodiments of the present disclosure have been described above, it goes without saying that the present disclosure is not limited to the above-described embodiments and can take various forms.
[0083] (2a) In addition to the aluminum alloy sheet of the above embodiment, the present disclosure also includes various embodiments of a member constituted by this aluminum alloy sheet, a manufacturing method of this aluminum alloy sheet, and the like.
[0084] (2b) The function of one component in the above embodiments may be distributed among multiple components, or the functions of multiple components may be integrated into one component. In addition, a part of the configuration of the above embodiments may be omitted. In addition, at least a part of the configuration of the above embodiments may be added to or substituted for the configuration of another of the above embodiments. Note that all aspects included in the technical idea identified from the wording of the claims are embodiments of the present disclosure.
[0085] 3. Working Examples The following describes the content of the tests conducted to confirm the effects of the present disclosure and their evaluation.
[0086] <Production of aluminum alloy sheets> As examples and comparative examples, aluminum alloy sheets S1 to S22 shown in Tables 1 and 2 were produced. Specific production procedures are described below.
[0087] First, an ingot containing the components (% by mass) of Alloy Nos. 1-11 shown in Table 3, with the remainder being aluminum and unavoidable impurities, was produced by semi-continuous casting. The ingot contained 0.10% by mass or less of Ti, 0.25% by mass or less of Zn, 0.10% by mass or less of Cr, and 0.15% by mass or less of unavoidable impurities.
[0088] Next, the four faces of the ingot were chamfered. After that, the ingot was placed in a furnace and subjected to homogenization treatment. The homogenization temperature is shown in Table 1. After the homogenization treatment, the ingot was removed from the furnace and immediately hot rolling was started to produce a rolled sheet.
[0089] The obtained rolled sheet was annealed. The annealing temperature was as shown in Table 1, and the annealing time was 30 seconds. After annealing, the rolled sheet was cooled to room temperature by air cooling. After cooling, the rolled sheet was cold rolled. The target total reduction in cold rolling was as shown in Table 1. The product sheet thickness after cold rolling (i.e., t1 in formula (6)) was in the range of approximately 0.245 ± 0.01 mm. During cold rolling and after the final cold rolling, the temperature rise shown in Table 1 was applied.
[0090] After cold rolling, paint was applied to the sheet surface and a paint baking treatment was performed for 30 seconds. The practical temperature (PMT) during paint baking is shown in Table 1. By baking the paint, S1-S22 aluminum alloy sheets were obtained.
[0091] [Table 1]
[0092] [Table 2]
[0093] [Table 3]
[0094] <Evaluation of aluminum alloy sheets> (Tensile properties) A No. 5 test piece as specified in JIS-Z-2241:2011 was prepared from the S1-S22 aluminum alloy plate. This test piece extends in a direction that forms an angle of 0° with respect to the rolling direction. A tensile test was performed on this test piece in accordance with JIS-Z-2241:2011 to measure the 0.2% proof stress and tensile strength. 0.2% proof stress σ 0.2 and tensile strength σ B The measurement results and the average value of 0.2% yield strength and tensile strength σ fm is shown in Table 1.
[0095] For the aluminum alloy plates S1-S22, the plate thickness was measured using a microgauge, and the value V(=t 2.27 ×σ fm / (σ 0.2 / σ B )) was calculated. The calculation result of the value V and σ fm / (σ 0.2 / σ B ) values are shown in Table 2.
[0096] (Toughness) In the aluminum alloy plate of S1-S22, the area is 0.3 μm by the measurement method described in the embodiment. 2 The ratio (area ratio) of the total area of the cross section of the above Mg2Si particles was calculated. The measurement results are shown in Table 2.
[0097] For the aluminum alloy sheets S1-S22, the earing ratio was calculated from the measurement method described in the embodiment and the left side of the formula (2). The results are shown in Table 2. In the table, "-" indicates that the measurement was not performed.
[0098] For the aluminum alloy sheets S1-S22, the number of repeated bending cycles was calculated from the measurement method and formulas (4) and (5) described in the embodiment. The results are shown in Table 2. In the table, "-" indicates that the measurement was not performed.
[0099] (scrap mixture ratio) Regarding the composition of the aluminum alloy plate of S1-S22, it was judged whether the possible mixing ratio of 3104 aluminum alloy scrap was 50 mass% or more. The results are shown in Table 2.
[0100] In Table 2, aluminum alloy plates marked with "≧50" can contain 50 mass% or more of 3104 aluminum alloy. The possible content of 3104 aluminum alloy scrap is determined based on Table 4.
[0101] Table 4 shows the relationship between the blend ratio of 3104 aluminum alloy and 5182 aluminum alloy and the average value of the component specifications. The first line of Table 4 shows the average value of the component specifications of 3104 aluminum alloy, and the second line shows the average value of the component specifications of 5182 aluminum alloy.
[0102] For example, when the blend ratio of 3104 aluminum alloy is 50 mass%, the average value of Si is 0.20 mass%, the average value of Fe is 0.29 mass%, the average value of Cu is 0.11 mass%, the average value of Mn is 0.7 mass%, and the average value of Mg is 2.8 mass%.
[0103] Therefore, when the ratio of each component of the aluminum alloy plate is equal to or greater than the above values of Si, Fe, Cu, Mn, and Mg, the possible blending ratio of the 3104 aluminum alloy plate is 50% by mass or more. As the blending ratio of the 3104 aluminum alloy increases, the contents of Si, Fe, Cu, and Mn increase and the content of Mg decreases. The aluminum alloy plates of S1 and S15-S22 can blend 50% by mass or more of the 3104 aluminum alloy scrap.
[0104] [Table 4]
[0105] (Pressure resistance) The pressure resistance of the aluminum alloy sheets S1-S22 was measured by the measurement method described in the embodiment. The results are shown in Table 2. The aluminum alloy sheets S1, S7-S9, and S15-S22 exhibited high pressure resistance of 550 kPa or more.
[0106] The value of equation (3) V(=t 2.27 ×σ fm / (σ 0.2 / σ B A graph showing the relationship between the value of V and the withstand voltage of the alloy plate is shown in Figure 3. From Figure 3, it was confirmed that there is a high correlation between the value of V and the withstand voltage. Therefore, σ on the left side of Equation (1) fm / (σ 0.2 / σ B) is 350 MPa or more, a high pressure resistance of 550 kPa or more can be achieved without a significant increase in plate thickness.
[0107] The aluminum alloy sheets S20-S22, which were subjected to a higher homogenization temperature, showed significantly higher pressure resistance. The aluminum alloy sheet S1, which was subjected to a higher annealing temperature after hot rolling, showed high strength and pressure resistance even with a low Mg content.
[0108] For all aluminum alloys, the lower the paint baking temperature (PMT), the higher the strength. For example, when comparing aluminum alloy sheets S15-S17 and S20-S22, the lower the paint baking temperature, the higher the pressure resistance.
[0109] The area ratio of Mg2Si particles was small, less than 1.0%, in the S1-S3, S6-S14, and S20-S22 aluminum alloys. Among the S15-S22 aluminum alloys, the S20-S22 aluminum alloy sheet, which had been subjected to a high homogenization temperature, had a particularly small area ratio of Mg2Si particles.
[0110] Therefore, when comparing the aluminum alloy plate S18 and the aluminum alloy plate S21, the number of repeated bending cycles was equal to or greater than that of the aluminum alloy plate S21, even though the pressure resistance of the aluminum alloy plate S21 was nearly 50 kPa higher than that of the aluminum alloy plate S18. In addition, the aluminum alloy plate S8 also had a smaller area ratio of Mg2Si particles, so the number of repeated bending cycles was greater than that of the aluminum alloy plate S17, despite its high pressure resistance. [Explanation of symbols]
[0111] 1…Eriksen Cup.
Claims
1. The silicon (Si) content is 0.20% by mass or more and 0.40% by mass or less, The iron (Fe) content is 0.29% by mass or more and 0.70% by mass or less, The copper (Cu) content is 0.11 mass% or more and 0.40 mass% or less, The manganese (Mn) content is 0.7% by mass or more and 1.2% by mass or less, The magnesium (Mg) content is 1.1% by mass or more and 4.0% by mass or less, The balance is aluminum and unavoidable impurities, 0.2% proof stress σ 0.2 , tensile strength σ B , and the average value of 0.2% proof stress and tensile strength σ fm satisfies the following formula (1), A paint-baked aluminum alloy sheet for can ends, in which in a cross section of a surface layer parallel to the sheet surface, the proportion of the total area of Mg 2 Si particles having an area of 0.3 μm 2 or more in said cross section is 1.0% or less. s fm / (s 0.2 / s B )≧350MPa・・・(1)
2. The aluminum alloy sheet for can ends according to claim 1, The average value h of the maximum sidewall height in the circumferential direction of the Erichsen cup formed by the Erichsen test in the region around 0° and the region around 180° with respect to the rolling direction 0p and the average value h of the maximum sidewall heights in the region around 45°, the region around 135°, the region around 225°, and the region around 315° with respect to the rolling direction. 45p and the average value h of the minimum sidewall height in each of the regions of 0° to 45°, 45° to 135°, 135° to 180°, 180° to 225°, 225° to 315°, and 315° to 360° with respect to the rolling direction. v and a paint-baked aluminum alloy sheet for can ends, which satisfies the following formula (2): (h 0p -h 45p ) / h v ×100≧-7.0 ・・・(2)
3. The aluminum alloy sheet for can lids according to claim 1 or 2, The Si content is 0.20 mass% or more and 0.40 mass% or less, The Fe content is 0.30 mass% or more and 0.70 mass% or less, The Cu content is 0.11 mass% or more and 0.40 mass% or less, The Mn content is 0.7 mass% or more and 1.2 mass% or less, A paint-baked aluminum alloy sheet for can ends, having a Mg content of 1.1% by mass or more and 3.0% by mass or less.
Citation Information
Patent Citations
Manufacture of aluminum alloy sheet having strength* ductility and formability
JP1980134149A
Manufacture of aluminum alloy rigid plate for molding
JP1985258454A
Can lid material excellent in bendability and its production
JP1996060284A
Aluminum alloy laminate for can cover adapted to recycling and manufacture thereof
JP1997070925A
Aluminum alloy-laminated sheet and its production
JP1999269594A